2020
DOI: 10.1002/adem.202000453
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Compression Performance and Energy Absorption of Lattice Structures Fabricated by Selective Laser Melting

Abstract: Figure 9. Energy absorption of Gyroid and IW structures to the compressive strains of 15% and 70%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 45 publications
3
24
0
Order By: Relevance
“…From these results, it was concluded that samples with a gyroid infill pattern were able to acheive a softer response than samples printed with a lines infill. This is consistent with other studies that found the gyroid structure to be softer than both diamond and primitive (grid and lines) lattice structures (Shi et al, 2020). Conclusions from the test report stated that the varioshore TPU printed samples could achieve similar properties to that of the materials currently used to manufacture orthotics, such as Poron foams and EVAs, but further development of softer samples is needed to obtain a suitable material stiffness range for orthotic production.…”
Section: Resultssupporting
confidence: 87%
“…From these results, it was concluded that samples with a gyroid infill pattern were able to acheive a softer response than samples printed with a lines infill. This is consistent with other studies that found the gyroid structure to be softer than both diamond and primitive (grid and lines) lattice structures (Shi et al, 2020). Conclusions from the test report stated that the varioshore TPU printed samples could achieve similar properties to that of the materials currently used to manufacture orthotics, such as Poron foams and EVAs, but further development of softer samples is needed to obtain a suitable material stiffness range for orthotic production.…”
Section: Resultssupporting
confidence: 87%
“…[82] The compressive mechanical performance and energy absorption capacity of TPMS structures with and without density gradients have been investigated in numerous studies. For instance, quasistatic compressive behaviors of four different TPMS lattice structures were analyzed experimentally and numerically by Shi et al [83] While gyroid, diamond, and I-wrapped (IW) structures have a bending-torsional coupling deformation mode due to their relative density, gyroid and IW structures showed improved compressive mechanical performance but lowered energy absorption capacities. Yu et al [84] investigated the mechanical properties and energy absorption capacity of uniform and density-graded Schwarz-primitive and gyroid lattice structures (Figure 4b).…”
Section: Definitions Types and Mechanical Characterizationmentioning
confidence: 99%
“…In relationship with the previous studies of the capability of TPMS to absorb energy, it must be highlighted that, despite there are some experimental studied of the behavior of these materials under quasi static load or with a low strain rate (0.001 s -1 to 0.01 s -1 ) 20,26,30 , there are only a few that study these materials under dynamic loads and analyzes the influence of the strain rate. In the case of McKown et al 19 , they study the behavior of octahedral lattice structure under quasi-static and low strain rate (0.001 to 0.5 s -1 ) load cases and also under blast loading (10 3 s -1 ) using a drop tower.…”
Section: Introductionmentioning
confidence: 99%